ChemInform Abstract: In Vitro Propagation of Genus Ceropegia and Retrosynthesis of Cerpegin ‐ a Review. Issue 3 (January 2015) - Muthukrishnan, S.; Franklin Benjamin, J. H.; Sathishkannan, G.; Senthil Kumar, T.; Rao, M. V.
Abstract Review: 83 refs.